Synthesis and Characterization of CuO-ZnO Nano Additive for Lubricant - Shrestha, Buddha Kumar; Trital, Hira Mani; Rajbhandari, Armila (Scientific World, 2020)
A mixed metal oxide (CuO-ZnO) additives has been successfully synthesized in laboratory by co-precipitation technique. The optimum ratio of CuO and ZnO in mixed metal oxide was found to be 1:1. The sodium lauryl sulfate (SLS) has been used as surfactant. The obtained material was found to be crystalline having crystalline size of 18 nm. The stretching band in FTIR spectra at around 1072 cm-1 to 750 cm-1 and around 600 cm-1 indicates the presence of Zn-O and Cu-O bonds. As prepared nano-particles have been used as nano additive in base oil to improve physio-chemical parameters of lubricants. The results revealed that the additive blended base oil (lubricant) has shown excellent lubrication properties. The higher kinematic viscosity of 33.0504 and 6.0158 at 40°C and 100°C respectively showed that as prepared additive blended lubricant is of ISO-32 category according to ISO grading system for lubricants. Similarly, viscosity index was found to be improved from 101 to 129. The pour point was found to be significantly decreased from -6°C to -24°C. So it can be used as good pour point depressant and could be used even in the extreme cold environment condition. The flash point was found to be increased from 215°C to 220°C indicating that the prepared mixed metal oxide (CuO-ZnO) acts as flash point enhancer. The copper strip corrosion rating was found to be 1b for additive indicating the non corrosive nature. The absence of moisture and pH around the neutral range 6.18 showed the additive blended lubricant is not harmful for machinery devices.